What is the Value of Community Oximetry Monitoring in People with SARS-Cov-2? – A Prospective, Open-Label Clinical Study - Wilcock, Jane; Grafton-Clarke, Ciaran; Coulson, Tessa (Archives of Clinical and Biomedical Research, 2021)
Background: In people with COVID-19, hypoxia at the time of admission is known to be related to mortality. Monitoring of oxygen saturations (SpO2) is therefore an increasingly common part of community- based care, with the aim of improving the identi-fication of adults who are deteriorating. We set out to investigate whether rigid SpO2 triggers, or absolute change in SpO2, is more indicative of deterioration in COVID-19. Methods: A prospective, uncontrolled, open-label study in a large UK general practice was conducted between May and November 2020. Participants recor-ded twice daily oximetry and symptom diary for 14 days after test-confirmed COVID-19. Primary out-comes were the proportion of people whose SpO2 dropped to ≤ 94% and ≤ 92%, the average maximum reduction in SpO2, and admission to hospital. We also investigated the relationship between MRC Dyspnoea scale, modified Roth score, and SpO2 through corre-lation analyses. Results: 52 participants were recruited, following which 41 participants completed the study. The average age was 45.9 years with 63.4% identifying as female. The mean maximum reduction in SpO2 was 2.8%. The average time to maximum reduction in SpO2 was 6.4 days. Nine participants (22.0%) had a reduction in SpO2 to ≤ 94%. Three of these had a reduction in SpO2 to ≤ 92%, for which all three were admitted to hospital. Modified Roth score and SpO2 were weakly positively correlated (.31). MRC dysp-noea scale score and SpO2 were moderately negatively correlated (-.53). Conclusions: A reduction in SpO2 to ≤ 92% was found to be highly predictive for admission to hospital. Modified Roth score or MRC dyspnoea scale scores should not be used as proxy measures for oximetry. This study contributes to the ongoing narrative around community-based oximetry and provides insight and recommendations for those currently engaging in or planning to roll ou